Self-employment of economically active population in the region - Shelomentseva, V.P.; Bespalyy, S.V.; Beisembayeva, G.M.; Soltangazinov, A.R. (BUKETOV BUSINESS REVIEW, 2019)
The article is devoted to the research of the features of self-employed population in the region. The purpose of the research is to identify the problems of the inefficiently self-employed economically active population and to develop practical recommendations for this population’s transfer to efficiently self-employed and employed population. The authors of the article analyzed the main indicators of the labor market in the regions of Kazakhstan, the dynamics of the number of the self-employed population depending on the status of employment for 2010–2017, as well as the impact of the regional urbanization level on the level of selfemployment of the population. Data on the self-employed population of Pavlodar region on the basis of the following indicators: economically active population, employed population, wage and salary earners, selfemployed population, unemployed population, targeted social assistance recipients, low-income families living below the subsistence level are analyzed. The research identified systemic problems affecting both the labor market in Pavlodar region and the further economic growth of the region. Recommendations and proposals have been developed for the transfer of the inefficiently self-employed population into efficiently selfemployed and employed in the state employment programs’ population that will make it possible to apply the potential of inefficiently self-employed and unemployed citizens as an additional reserve for the region’s economic growth.